Q-switched and mode-locked thulium-doped fiber laser with pure Antimony film Saturable absorber - Rahman, Mohd Fauzi Ab; Latiff, Anas Abdul; Zaidi, Umi Zhalilah Mohd; Rusdi, Muhammad Farid Mohd; Rosol, Ahmad Haziq Aiman; Bushroa, Abdul Razak; Dimyati, Kaharudin; Harun, Sulaiman Wadi (Elsevier, 2018)
Stable and compact Q-switched and mode-locked thulium-doped fiber laser (TDFL) is demonstrated by employing Antimony (Sb) film Saturable absorber (SA) in the ring cavity. The Sb film SA is fabricated by sputtering a thin layer of Sb element onto polyvinyl alcohol (PVA) thin film. Self-pushed TDFL Q-switched with repetition rate and pulse width of 14.5 kHz to 23.5 kHz and 11.6 μs to 4.9 μs respectively are obtained, as the pump power raises from the threshold (271 mW) to its maximum (399 mW). The TDFL Q-switched spectrum is centered at 1947 nm wavelength. At the maximum pump power (399 mW), the maximum peak power and the maximum pulse energy are obtained at 24.4 mW and 120.12 nJ respectively. Meanwhile, self-starting mode-locked TDFL emerges as the pump power varies from 454 mW to 582 mW. The TDFL mode-locked output spectrum is centered at 1914 nm wavelength. A nearly constant repetition rate of 8.65 MHz and pulse width of 64 ps are observed, as the pump power lifted to the maximum (582 mW). The results verify that the pure Sb PVA film SA is viable to construct stable and reliable short pulse laser in the 2-micron regime.